Study of Impacts of Ganoderma applanatum (Pres.) Pat. Extract on Hepatic and Renal Biochemical Parameters of Rats - Sukumar Dandapat; Manoj Kumar; Rakesh Ranjan; Manoranjan Prasad Sinaha (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Traditionally, Ganoderma applanatum was used as medicinal supplement for treatment of different diseases. In this study, biochemical screening, acute toxicity, and impact of G. applanatum aqueous extract on liver and renal parameters were studied. Qualitative screening of G. applanatum aqueous extract showed presence of various biochemicals such as tannin, phenolics, proteins, flavanoids and other biochemicals. FTIR analysis also showed spectrum transmission peaks for different mycochemicals such as3248. 13cm-1 for phenol O-H stretch, 1597.06cm-1 for primary amine N-H stretch, 783.10cm-1 for aromatic (meta disub benzene) C-H stretch. The extract increased body weight (Initial body weight: 181.74g; final body weight: 185.08g) when compared to control group (Initial body weight: 178.61 g; final body weight: 181.14 g) in acute toxicity test dose (2000mg/kg). Similar insignificant in final body weight of animals of different groups were observed when compared to initial body weight of animals used for the study of live and renal profile. The extract had no significant effect on organ weight. Low dose (200mg kg-1) of extract insignificantly decrease AST (51.71±0.61 mg dL-1), ALT (146.07±0.89 mg dL-1), ALP (174.68±0.65 mg dL-1) and bilirubin (0.61±0.01 mg dL-1) level and significantly elevated serum albumin level (6.63±0.22 g dL-1) compare to control group. Low dose (200mg kg-1) extract showed similar insignificant decrease in serum urea (61.30±1.05 mg dL-1) and creatinine level (0.90±0.02 mg dL-1) and significantly decreased serum uric acid level (19.52±1.14 mg dL-1) compare to control group of rats. Thus, dose-oriented application of G. applanatum extract can be beneficial for treatment of hepatic and renal diseases.